Organization of the mitochondrial genome of Atlantic cod, Gadus morhua. - Johansen, S (1990)
The mitochondrial DNA (mtDNA) from the Atlantic cod, Gadus morhua, was mapped using 11 different restriction enzymes and cloned into plasmid vectors. Sequence data obtained from more than 10 kilobases of cod mtDNA show that the genome organization, genetic code, and the overall codon usage have been conserved throughout the evolution of vertebrates. Comparison of the derived amino acid sequences of proteins encoded by cod mtDNA to the ones encoded by Xenopus laevis mtDNA revealed that the amino acid identity range from 46% to 93% for the different proteins. ND4L is most divergent while COI is most conserved. GUG was found as the translation initiation codon of the COI gene, indicating a dual coding function for this codon. The sequences of the 997 base pair displacement-loop (D-loop)-containing region and the origin of L-strand replication (oriL), are presented. Only few of the primary and secondary structure features found to be conserved among mammalian mitochondrial D-loops, can be identified in cod. Presence of CSB-2 in the D-loop-containing region and the conserved hairpin structure at oriL, indicates that replication of bony fish mtDNA may follow the same general scheme as described for higher vertebrates.